State-of-the-art Advances in Duchenne Muscular Dystrophy - Henriette Van Ruiten; Katherine Bushby; Michela Guglieri (European Medical Journal, 2017)
Duchenne muscular dystrophy (DMD) is a severe and fatal muscle condition affecting young children. Without interventions, affected boys lose the ability to walk independently by the age of 10 and develop progressive cardiac and respiratory failure. The last 20 years have seen a change in the natural history of DMD following improvements in clinical care and proactive interventions to manage complications of the disease. An international collaboration of DMD experts has created care imperatives for best practice in DMD; these are now available in 30 different languages and are disseminated worldwide. An update of these care recommendations is currently under review.